Targeted search of hypoglycemic agents among N-substituted isoindoline-1,3-diones and its analogues - Martynenko, Yu. V.; Kazunin, M. S.; Antypenko, O. M.; Selivanova, Ye. A.; Kovalenko, S. I.; Trzhetsynskyi, S. D.; Мартиненко, Юлія Вікторівна; Казунін, Максим Станіславович; Антипенко, Олексій Миколайович; Селіванова, Є. А.; Коваленко, Сергій Іванович; Тржецинський, Сергій Дмитрович; et al. (Запорізький державний медичний університет, 2018)
It is known, that increasing of glucose level in the blood is an important factor at the risk of vascular complications in diabetes mellitus type 2 development. Taking this into account, short-acting priming regulators of glycemia (meglitinides) are designed, such as tableted sugar-reducing drugs with short acting insulin secretion stimulation. They are characterized by a slight decrease of glycohemoglobin content, the risk of body weight gain and decrease of efficacy during long-term usage despite their effectiveness. The solution of this problem can be as following: the creation of more effective drugs, which would contain known antidiabetic “pharmacophore” fragments able to provide a long-term hypoglycemic effect and having a polyvectoral mechanism of activity and effect both on symptoms of the disease and on disease etiology. The aim of the work is targeted search of hypoglycemic isoindoline-1,3-dione derivatives and its hydrogenated analogues based on rational design, structural similarity to metglitinides, molecular docking and traditional pharmacological screening. Materials and methods: laboratory utensils and organic solvents, “Stuart Scientific SMP30” melting point apparatus, ELEMENTAR vario EL Cube elemental analyzer, Bruker ALPHA FT-IR spectrometer, Varian-Mercury 400 1H NMR spectrometer, Agilent 1100 Series liquid chromatograph, Marvin Sketch 17.21, AutoDockTools-1.5.6, Discovery Studio 4.0. Results. The targeted search of hypoglycemic agents among N-substituted isoindoline-1,3-diones and its analogues based on the structural similarity with existing active pharmaceutical ingredients, using molecular docking and traditional pharmacological screening was performed in the work. Mentioned compounds were synthesized by the refluxing of phthalic anhydride and its analogs with aminoalkyl-(alkaryl-,aryl-) carboxylic acids in the medium of the acetic acid. It was shown, that refluxing of 3a,4,7,7a-tetrahydro-4,7-epoxyisobenzofuran-1,3-dione with glycine under the given conditions resulted the retro Diels-Alder reaction and formation of (Z)-4-((carboxymethyl)amino)-4-oxobut- 2-enoic acid. Elemental analysis, chromatomass-, IR- and 1H-NMR spectral methods were used to prove the structure and individuality of the synthesized compounds. Conclusion. A number of compounds were synthesized and chemically modified. Research of their hypoglycemic activity was carried out, that raveled a number of high active substances. Certain "structure – activity relations" were established and the perspective directions of their further chemical modification were substantiated. Відомо, що підвищення рівня глюкози у крові – важливий чинник ризику розвитку судинних ускладнень при цукровому діабеті 2 типу. Враховуючи це, розробили регулятори глікемії (меглітиніди) – цукрознижувальні засоби, механізм дії котрих спрямований на стимулювання секреції інсуліну протягом короткого проміжку часу. Незважаючи на ефективність, для них характерне незначне зменшення вмісту глікогемоглобіну, ризик набору маси тіла та зниження ефективності під час тривалого застосування. Вирішення цієї проблеми можливе тільки шляхом створення ефективніших препаратів, котрі б поєднували відомі антидіабетичні "фармакофорні" фрагменти, що здатні забезпечувати тривалий гіпоглікемічний ефект, впливати на симптоми захворювання і причини їх виникнення. Мета роботи – спрямований пошук гіпоглікемічних агентів серед похідних ізоіндолін-1,3-діонів і його гідрованих аналогів на основі раціонального дизайну, структурної подібності до метглітинідів, молекулярного докінгу та традиційного фармакологічного скринінгу. Матеріали та методи. Лабораторний посуд та органічні розчинники, апарат для визначення температури плавлення "Stuart Scientific SMP30", елементний аналізатор ELEMENTAR vario EL Cube, ІЧ спектрометр Bruker ALPHA FT-IR, 1Н ЯМР-спектрометр Varian-Mercury 400, рідинний хроматограф Agilent 1100 Series, програмне забезпечення Marvin Sketch 17.21, Hyper Chem 8.0.8, AutoDockTools-1.5.6, Discovery Studio 4.0. Результати. Виконали спрямований пошук гіпоглікемічних агентів серед N-заміщених ізоіндолін-1,3-діонів і його аналогів на основі структурної подібності з наявними активними фармацевтичними інгредієнтами з використанням молекулярного докінгу, традиційного фармакологічного скринінгу. Сполуки синтезували взаємодією фталевого ангідриду та його аналогів з аміноалкіл-(алкаріл-,арил-) карбоновими кислотами при нагріванні в оцтовій кислоті. Показано, що при нагріванні 3a,4,7,7a-тетрагідро-4,7-епоксиізобензофуран-1,3-діону з гліцином при заданих умовах відбувається реакція ретро Дільса–Альдера та утворюється (Z)-4-((карбоксиметил) аміно)-4-oксобут-2-енова кислота. Будову та індивідуальність синтезованих сполук доведено елементним аналізом, хромато-мас, ІЧ- і 1Н-ЯМР спектральними методами. Висновки. У результаті досліджень синтезували та хімічно модифікували ряд сполук, вивчили їхню гіпоглікемічну активність, виявили ряд високоактивних речовин, встановили певні закономірності "структура – дія" та обґрунтували перспективні напрями хімічної модифікації. Известно, что повышение уровня глюкозы в крови является важным фактором риска развития сосудистых осложнений при сахарном диабете 2 типа. С учетом этого разработаны короткодействующие регуляторы гликемии (меглитиниды) – сахароснижающие средства, механизм действия которых направлен на стимулирование секреции инсулина в течение короткого промежутка времени. Несмотря на эффективность, для них характерно незначительное уменьшение содержания гликогемоглобина, риск набора массы тела и снижение эффективности при длительном применении. Решение этой проблемы возможно только путем создания более эффективных препаратов, объединяющих известные противодиабетические «фармакофорные» фрагменты, способные обеспечивать длительный гипогликемический эффект и влиять на симптомы заболевания и причины их возникновения. Цель работы – направленный поиск гипогликемических агентов среди производных изоиндолин-1,3-дионов и их гидрированных аналогов на основе рационального дизайна, структурного сходства с метглитинидами, молекулярного докинга и традиционного фармакологического скрининга. Материалы и методы: лабораторная посуда и органические растворители, аппарат для определения температуры плавления "Stuart Scientific SMP30", элементный анализатор ELEMENTAR vario EL Cube, ИК спектрометр Bruker ALPHA FT-IR, 1Н ЯМР спектрометр Varian-Mercury 400, жидкостный хроматограф Agilent 1100 Series, программное обеспечение Marvin Sketch 17.21, Hyper Chem 8.0.8, AutoDockTools-1.5.6, Discovery Studio 4.0. Результаты. Проведен направленный поиск гипогликемических агентов среди N-замещенных изоиндолин-1,3-дионов и их аналогов на основе структурного сходства с существующими активными фармацевтическими ингредиентами с использованием молекулярного докинга и традиционного фармакологического скрининга. Указанные соединения синтезированы взаимодействием фталевого ангидрида и его аналогов с аминоалкил-(алкарил-,арил) карбоновыми кислотами при нагревании в уксусной кислоте. Показано, что при нагревании 3a,4,7,7a-тетрагидро-4,7-эпоксиизо-, бензофуран-1,3-диона с глицином при заданных условиях протекает реакция ретро Дильса–Альдера и образуется (Z)-4-((карбоксиметил)амино)-4-oксобут-2-еновая кислота. Строение и индивидуальность синтезированных соединений доказано элементным анализом, хромато-масс, ИК- и 1Н-ЯМР спектральными методами. Выводы. В результате исследований синтезированы и химически модифицированы соединения, проведены исследования на их гипогликемическую активность, выявлен ряд высокоактивных веществ, установлены определенные закономерности "структура – действие" и обоснованы перспективные направления их дальнейшей химической модификации.
Cпрямований пошук гіпоглемічних агентів серед N-заміщених ізоіндолін-1,3-діонів та їх аналогів
Направленный поиск гипогликемических агентов среди N-замещенных изоиндолин-1,3-дионов и их аналогов
Keywords: carboxylic acids; molecular docking simulation; synthesis; magnetic resonance spectroscopy; hypoglycemic agents; карбоновые кислоты; молекулярной стыковки моделирование; синтез; магнитно-резонансная спектроскопия; гипогликемические средства; карбонові кислоти; молекулярне док-моделювання; синтез; магнітно-резонансна спектроскопія; гіпоглікемічні засоби